(untitled) (Bangladesh Journal of Agricultural Research, 2010)
Rhizoctonia solani isolates were collected from soil of different agro-ecological zones of Bangladesh and also from infected plant parts of different crops and grasses. Collected isolates were classified into five different cluster groups on the basis of morphological and cultural characters. Five isolates taking one from each of the five different cluster groups were selected to study their pathogenicity and host range on 35 different crops. Pathogenicity and host range of the isolates were determined by planting the seeds in water agar plate infested with R. solani isolates and incubated at 25°C temperatures. After analyzing the morphological and cultural characters of the isolates, it was found that there was no relations between the isolates with respect to their origin from where they were collected. It indicated that the diversity among the isolates was not correlated with their origin. In case of host range and pathogenicity among the five selected isolates of different cluster groups, the isolate JES-16 was an avirulent isolate. The isolate SYL-30 had narrow host range and a low virulent isolate. The isolates DIN-8 and GAZ-18 possessed wide host range and might be considered as virulent isolates. The isolate GAZ-9 was a highly virulent isolate with a wide host range. Keywords: Rhizoctonia solani; morphological and pathogenic variations; isolates. DOI: 10.3329/bjar.v35i3.6443 Bangladesh J. Agril. Res. 35(3) : 375-380